2018
DOI: 10.1111/cob.12249
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Obesity Services in Public Hospitals in Australia: a position statement based on expert consensus

Abstract: We aimed to describe the current state of specialist obesity services for adults with clinically severe obesity in public hospitals in Australia, and to analyse the gap in resources based on expert consensus. We conducted two surveys to collect information about current and required specialist obesity services and resources using open-ended questionnaires. Organizational level data were sought from clinician expert representatives of specialist obesity services across Australia in 2017. Fifteen of 16 represent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
64
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(68 citation statements)
references
References 21 publications
(26 reference statements)
4
64
0
Order By: Relevance
“…This was in large part due to the referred patients not meeting the COMS eligibility criteria, with a range of referrals received for non‐adults, for those with a BMI below the severe obesity range and/or for those without obesity‐related comorbidities. Prolonged wait times are known to impact attendance, and therefore, the duration between referral and initial medical review observed in our study is likely to have further contributed to the reduced number of patients attending initial medical review.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…This was in large part due to the referred patients not meeting the COMS eligibility criteria, with a range of referrals received for non‐adults, for those with a BMI below the severe obesity range and/or for those without obesity‐related comorbidities. Prolonged wait times are known to impact attendance, and therefore, the duration between referral and initial medical review observed in our study is likely to have further contributed to the reduced number of patients attending initial medical review.…”
Section: Discussionmentioning
confidence: 89%
“…Recent data from Australia indicate that the prevalence of obesity has increased from 19% in 1995 to 28% in 2014‐2015 . In an effort to address this obesity epidemic, several Australian state and territory Health Departments have introduced publicly funded specialist obesity services …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Australia, these services have arisen ad hoc and include services in both the public and private health sector. Specialist obesity services in public hospitals in Australia have been described in detail by the Clinical Obesity Services in Public Hospitals (COSiPH) collaborators, including variations in the composition of services, limitation of access to obesity services by geography, disease severity and cost and inadequate resourcing of clinics, including both staff and infrastructure, along with recommendations for improvements . One of the recommendations put forth by the panel of experts in the COSiPH Working Group was a systematic capturing of minimum and standardized clinical data for ongoing monitoring and evaluation within services and to promote collaboration between services, such as information sharing for quality assurance as well as data linkage for future research purposes.…”
Section: Introductionmentioning
confidence: 99%